Dependence of Viscosity and Diffusion on β-Cyclodextrin and Chloroquine Diphosphate Interactions - Musilová, Lenka (2021)
Mutual diffusion coefficients of chloroquine diphosphate (CDP) in aqueous solutions both without and with b-cyclodextrin (b-CD) weremeasured at concentrations from(0.0000 to 0.0100)mol dm3 and 298.15 K, using the Taylor dispersion technique. Ternary mutual diffusion coefficients (Dik) measured by the same technique are reported for aqueous CDP + b-CD solutions at 298.15 K. The presence of b CD led to relevant changes in the diffusion process, as showed by nonzero values of the cross-diffusion coefficients, D12 and D21. b-CD concentration gradients produced significant co-current coupled flows of CDP. In addition, the effects of b-CD on the transport of CDP are assessed by comparing the binary diffusion coefficient of aqueous CDP solutions with the main diffusion coefficient (D11) measured for ternary {CDP(1) + b-CD(2)} solutions. These observations are supported by viscosity analysis. All data allow to have a better interpretation on the effect of cyclodextrin on the transport behavior of CDP.